D.W. Winnicott : a Biographical Portrait. - Kahr, Brett (Karnac Books, 1996)
A distillation of painstaking research into the life of Donald Winnicott, tracing his life from his childhood in Plymouth, through his career in paediatrics, to his election as President of the British Psycho-Analytic Society. The author makes many interesting links between Winnicott's life and the development of his theories.